Ответы и объяснения

2013-04-07T21:29:35+04:00

\frac{(-\sqrt{3})\cdot5\sqrt{3}}{5\sqrt{3}-(-\sqrt{3})}\cdot(\frac{5\sqrt{3}}{-\sqrt{3}}-2+\frac{-\sqrt{3}}{5\sqrt{3}})=\frac{(-\sqrt{3})\cdot5\sqrt{3}}{5\sqrt{3}+\sqrt{3}}\cdot(\frac{5\sqrt{3}}{-\sqrt{3}}-2+\frac{-\sqrt{3}}{5\sqrt{3}})=\\\\ =\frac{(-\sqrt{3})\cdot(5\sqrt{3})^{2}}{(5\sqrt{3}+\sqrt{3})\cdot(-\sqrt{3})}-\frac{2\cdot(-\sqrt{3})\cdot5\sqrt{3}}{5\sqrt{3}+\sqrt{3}}+\frac{(-\sqrt{3})^{2}\cdot5\sqrt{3}}{(5\sqrt{3}+\sqrt{3})\cdot5\sqrt{3}}=

 

=\frac{(-\sqrt{3})\cdot25\cdot3}{(5\sqrt{3}+\sqrt{3})\cdot(-\sqrt{3})}-\frac{2\cdot(-\sqrt{3})\cdot5\sqrt{3}}{5\sqrt{3}+\sqrt{3}}+\frac{(-3)\cdot5\sqrt{3}}{(5\sqrt{3}+\sqrt{3})\cdot5\sqrt{3}}=

 

Приводим каждую дробь к общему знаменателю:

 

(5\sqrt{3}+\sqrt{3})\cdot5\sqrt{3}\cdot(-\sqrt{3})

 

Получаем:

 

(-\sqrt{3}\cdot5\sqrt{3}\cdot25\cdot3)-(2\cdot(-\sqrt{3})^{2}\cdot(5\sqrt{3})^{2})+(-3\cdot5\sqrt{3}\cdot(-\sqrt{3}))=\\\\ ((-\sqrt{3\cdot25\cdot3})\cdot25\cdot3)-(2\cdot(-3)\cdot25\cdot3)+(-3\cdot(-\sqrt{3\cdot25\cdot3}))=\\\\ ((-\sqrt{9\cdot25})\cdot25\cdot3)-(2\cdot(-3)\cdot25\cdot3)+(-3\cdot(-\sqrt{9\cdot25}))=\\\\ ((-3\cdot5)\cdot25\cdot3)-(2\cdot(-3)\cdot25\cdot3)+(-3\cdot(-3\cdot5))=\\\\ -1125-(-450)+45=-630

 

 

Ответ: -630